Potencial Evocado Auditivo de Longa Latência em crianças usuárias de implante coclear - Figueiredo, Sabrina Suellen Rolim (2015)
The use of amplification and implantable devices is an alternative to minimize the effects of sensory deprivation, imposed by hearing loss. The effects of sensory deprivation in the central auditory system have been studied by recording the latencies of Long Latency Auditory Evoked Potential (LLAEP) as a cortical maturation indicator. The assessment of auditory cortical development of the child user of cochlear implant (CI) can provide important data on the conditions of the upper ways, and the effectiveness of the strategy used after the intervention, through the use of hearing aids or CI. OBJECTIVE: To study the LLAEP in children with bilateral sensorineural hearing loss, severe and/or profound cochlear implant users. METHOD: This study is qualitative/quantitative, descriptive, using the LLAEP in children with sensorineural severe and/or profound hearing with cochlear implant. The participants were 8 children using unilateral cochlear implant, age ranging between 3 and 5 years old. Data were collected regarding the etiology, hearing age, chronological age at implantation, mean values of free field audiometry with CI, and the record of LLAEP in the free field as a transducer with the speech stimulus /ba/, in the intensity of 75 dBSPL, with the use of CI. The eye movement was recorded to control the generated artifact. RESULTS: The values of LLAEP latency were statistically analyzed and described according to the study variables. It was possible to identify the component P1 in all volunteers in the study. Regarding the N1 component, 50% of the patients showed responses allowing the registry. None of the participants presented the P2 component. There is a statistically significant correlation founded between the latency value of the N1 component and the time in which the participant had no use of hearing aids, waiting for the diagnosis. CONCLUSION: LLEAP may be useful in routine clinical audiology to monitor the central auditory development in children with cochlear implants. The effects of central auditory deprivation and changes in central auditory processing can be monitored by recording LLAEP and monitoring of other factors that influence the user's IC auditory performance